Parenting Attachment dan Subjective Well-Being Generasi Alpha - Ni Wayan Viola Aryanthi Putricia; Malida Fatimah; Sri Muliati Abdullah; Erydani Anggawijayanto (Publikasi Indonesia, 2025)
Generation Alpha grew up in the digital era with early exposure to technology that influences the way they interact and develop. Therefore, it is important for us to understand the factors that may affect their subjective well-being, including attachment to parents. The subjects of this study were 395 people belonging to the alpha generation, aged 11-14 years who had at least one parent living with them. The research instruments were the Inventory of Parent and Peer Attachment-Revised (IPPA-R) by Gullone & Robinson to measure parenting attachment and the Children’s World Subjective Well-Being Scale which is an adaptation by Borualogo & Casas to measure the level of subjective well-being in the alpha generation. Through statistical analysis of Spearman correlation, it was found that there was no significant relationship between parenting attachment and subjective well-being in the alpha generation (r = 0.079, p > .05).